Democratic Street: An application of Space Syntax in testing the spatial justice among women pedestrian - Khalid, Nurul Shakila; Nasrudin, Na’asah; Abdullah, Yusfida Ayu; Che Abdullah, Ishak (Environment-Behaviour Proceedings Journal, 2020)
This research examines the quality of streets and public life among women through observation. Axial analysis models are combined into Space Syntax to hypothesize the effect of grid layout on street vitality and sociability in shopping streets by using global and local integration to measure how women use the space. The result indicated that there is a correlation among these parameters with the following spatial configurative analyses; integrated streets attract more women pedestrians and how women feel as well as they use street space. Keywords: Democratic Street; Spatial Justice; Women; Space Syntax eISSN: 2398-4287 © 2020. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open-access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v5i13.1967